Using Primavera Software in Construction Scheduling, Access at Primavera (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Timely consideration of factors related to the effectiveness of construction and installation works in the construction industry is a key point in operational and production planning and management